2003
DOI: 10.1063/1.1613631
|View full text |Cite
|
Sign up to set email alerts
|

First compounds with argon–carbon and argon–silicon chemical bonds

Abstract: Argon is an extremely chemically inert element. HArF is presently the only experimentally known neutral molecule containing a chemically bound argon atom. Ab initio calculations at the MP2 and CCSD͑T͒ levels presented here suggest, however, the existence of whole families of additional molecules. Explicitly predicted are FArCCH, with an argon-carbon bond, and FArSiF 3 , with an argon-silicon bond. These metastable compounds are found to be protected from decomposition by relatively high energy barriers. Other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
47
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 29 publications
5
47
0
4
Order By: Relevance
“…A thermally stable solid-state configuration of HArF was also detected in an Ar matrix. 13 Since then, much argon-containing compounds such as HArCl, 14 HArCN, 15 FArCCH, 16 FArSiF 3 ,…”
Section: Introductionmentioning
confidence: 99%
“…A thermally stable solid-state configuration of HArF was also detected in an Ar matrix. 13 Since then, much argon-containing compounds such as HArCl, 14 HArCN, 15 FArCCH, 16 FArSiF 3 ,…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] The experimentally identified argon compounds are charged species, the exception being the neutral ground-state molecule HArF. 6,7 Additional neutral argon molecules FArCCH and FArSiF 3 were theoretically predicted by Cohen et al 8 HCCNgCN and HCCNgNC (Ng ) Ar, Kr, and Xe) are also computationally stable species; however, the experimental attempts to prepare them failed, whereas HNgCCCN molecules (Ng ) Kr and Xe) were identified. 9 The chemical bonds between a noble gas (Ng) and other atoms are usually quite weak, and examination of noble-gas chemistry benefits greatly from studies by cryogenic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…18 In this work, we report three new noble-gas compounds prepared in low-temperature matrices employing the HCCF precursor to make HCCNgF and HNgCCF molecules. The initial motivation was an attempt to prepare HCCArF predicted by Cohen et al 8 It was also interesting to compare the HNgCCF noble-gas hydrides with the previously reported HNgCCH species (Ng ) Kr and Xe) [19][20][21] with respect to the energetic stability and in view of the recent prediction of HXeCCH possibly being stable at room temperature. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Frohn and Theißen [40] have also calculated the geometric parameters and Mulliken charge distributions of the molecule. Cohen et al [41] have performed ab initio calculations at the MP2 and CCSD(T) levels and found that HCCArF and F 3 SiArF are metastable compounds protected from decomposition by relatively high energy barriers. Baker et al [42] have theoretically investigated the noble gas insertion compounds C 6 F 6 Ar n (n = 1-6) and found that all the compounds are aromatic according to the magnetic criterion.…”
Section: Introductionmentioning
confidence: 99%